Bridging Turmoil and Transformation: A Comprehensive Review of the Lebanese Banking Sector from 2000 to 2018 - Elia, Jean; Maalouf, Dr. Nada Jabbour Al; Sawaya, Dr. Chadia (International Journal of Membrane Science and Technology, 2023)
This article provides a thorough analysis of the Lebanese banking industry from 2000 to 2018. It looks at the major innovations, difficulties, and changes that have shaped the sector and shed light on the technological, economic, and regulatory factors that affect how well it performs. This study offers insights into opportunities and challenges faced by Lebanese banks within the domestic and regional financial landscape by analyzing trends, policies, and reforms. Between 2001 and 2019, data from published Bilanbanques were gathered, and this information is now being used to build theoretical foundations, empirical models, and a practical understanding of banking systems in emerging economies. The article's importance stems from its coverage of a crucial time in Lebanon marked by political transitions, economic downturns, and regional instability. It highlights how banks navigated difficult times and underwent transformative changes by thoroughly examining the banking industry within this context. Lebanese banks remained liquid, managed risks, and embraced modernization despite the recessionary conditions, positioning themselves for further expansion. Their perseverance during political unrest and economic downturns highlighted depositors' and investors' confidence, which was supported by adherence to international best practices. The Lebanese banking industry played a crucial role as a financial intermediary, catalyst, and partner throughout the years under consideration, promoting the expansion and stability of the economy. It was able to investigate domestic and international expansion opportunities thanks to its strong financial position, dedication to ethical business practices, and commitment to risk management. The sector's performance demonstrates how important it is to Lebanon's economy, serving as a rock of confidence and support for customers and investors in the face of local and regional unrest.